Three Musketeers for Lowering Cholesterol: Statins, Ezetimibe and Evolocumab - Xu, Qian; Deng, Yiming; Xiao, Jun; Liu, Xiangrui; Zhou, Min; Ren, Zhong; Peng, Juan; Tang, Yaling; Jiang, Zhisheng; Tang, Zhihan; Liu, Lushan (Current Medicinal Chemistry, 2021)
Coronary heart disease (CHD) is closely related to hypercholesterolemia, and lowering serum cholesterol is currently the most important strategy in reducing CHD. In humans, the serum cholesterol level is determined mainly by three metabolic pathways, namely, dietary cholesterol intake, cholesterol synthesis, and cholesterol degradation in vivo. An intervention that targets the key molecules in the three pathways is an important strategy in lowering serum lipids. Statins inhibit 3-hydroxyl-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase) to reduce low-density lipoprotein (LDL) by about 20% to 45%. However, up to 15% of patients cannot tolerate the potential side effects of high statin dosages, and several patients also still do not reach their optimal LDL goals after being treated with statins. Ezetimibe inhibits cholesterol absorption by targeting the Niemann–Pick C1-like 1 protein (NPC1L1), which is related to cholesterol absorption in the intestines. Ezetimibe lowers LDL by about 18% when used alone and by an additional 25% when combined with statin therapy. The proprotein convertase subtilisin/kexin type 9 (PCSK9) increases hepatic LDLR degradation, thereby reducing the liver’s ability to remove LDL, which can lead to hypercholesterolemia. Evolocumab, which is a PCSK9 monoclonal antibody, can reduce LDL from baseline by 53% to 56%. The three drugs exert lipid-lowering effects by regulating the three key pathways in lipid metabolism. Combining any with the two other drugs on the basis of statin treatment has improved the lipid-lowering effect. Whether the combination of the three musketeers will reduce the side effects of monotherapy and achieve the lipid-lowering effect should be studied further in the future.
Keywords: HMG-CoA reductase